HKSA ANALYSIS AND DOCKING OF ANTIOXIDANT ACTIVITY OF CURCUMIN ANALOGUES AGAINST TYROSINASE ENZYME - Chosya, Cahya; Roza, Destria; Nugraha, Asep Wahyu (Universitas Lampung, 2024)
Abstract : The aim of the HKSA and Docking analysis was to determine the potential of curcumin analogues as antioxidants for the activity of the tyrosinase enzyme. Predictor calculations were carried out using the hyperchem application with the CNDO semi-empirical geometric optimization method Multilinear regression analysis using SPSS to find the relationship between predictors and the activity of curcumin analogue derivative compounds as tyrosinase inhibitors. The best HKSA equation model is : LogIC50 : -3.195 – (1.135 x HOMO) + (1.064 x LUMO) - (0.239 x LogP) + (0.155 x HE) With a value of R = 0,984; R2 = 0,969; Adj R2 = 0,948; SE = 0,183; F count = 10,209; Sign = 0,000. This equation is used to predict new compounds derived from curcumin analogs that can be used as new tyrosinase inhibitors. The parameters for selecting this compound were because it had better activity and LogIC50 values compared to the parent compound. To see the affinity between the new curcumin analogue derivative compound and the tyrosinase enzyme, docking was carried out using Autodock Tools, which was visualized using Biovia discovery studio. The docking results show that the compound 2,5-bis (4-hydroxy 3-allyl benzylidene) cyclopentanone has potential inhibitory activity on the tyrosinase receptor as an antioxidant activity because it has the same amino acid residue as the original ligand (Tyrosine) with the binding energy of the compound 2,5- bis (4-hydroxy 3-allylbenzylidene) cyclopentanone is -5.92 kcal/mol and the Ki value is 46.03 uM, which is better than the binding energy of the compound (Tyrosine) which is -4.96 kcal/mol and the Ki value is 231.77 uM.Keywords: Curcumin, Tyrosinase, Antioxidant, QSAR, Docking DOI: 10.23960/jppk.v13i2.30560